A plan for observation of the Antarctic ozone hole in 1991 under the Polar Patrol Balloon (PPB) project - Hiroshi Kanzawa; Yutaka Kondo (National Institute of Polar Research, 1991)
Among the three Polar Patrol Balloon (PPB) experiments planned in the course of the 32nd Japanese Antarctic Research Expedition, one balloon will be launched from Syowa Station (69°S, 40°E) in September 1991 to observe depletion of the ozone layer over Antarctica-the so-called Antarctic ozone hole. In situ measurements will be made of ozone, aerosol, and temperature along the track of the balloon around the 50hPa level (∿18km) for about 10 days. The motivation for this exercise is as follows : Polar Stratospheric Clouds (PSCs) consist of aerosols which are formed in the cold polar lower stratosphere; the decrease of ozone in the Antarctic lower stratosphere in late winter and early spring, which is an aspect of the Antarctic ozone hole, is believed to be due to heterogeneous chemical processes occurring on the surface of PSCs. The PPB observation is a Lagrangian type observation, and it will be held around the 50hPa level where the ozone decreases most. Consequently, the ozone concentration measurement has the advantage that it will be able to detect the in situ chemical budget of ozone more directly than other types of observation. The aerosol instrument measures aerosol concentrations in the diameter range of 0.4-10 micron meters, devided into 7 classes to give detailed information on the microphysics and chemistry of PSCs. Data acquisition and balloon positioning will utilize the ARGOS system. The almost constant altitude of the zero-pressure balloon will be regulated with the help of an auto-ballast system.